KO‘ZNING OPTIK SISTEMASI VA TUZILISHI (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article talks about the structure of the optical system of the eye and its features. The eye is an optical system that creates an image of an object on the light-sensitive retina. The eye is surrounded by three membranes from the outside. The outer membrane is called sclera or protein membrane. The eye does not even perceive long-wavelength ultraviolet rays. The reason for this is that high-energy ultraviolet rays destroy light-sensitive pigments in the eye.